Introducing the “Franken‐Kiel” Carbonate Device: First Application to Δ47‐T Calibrations of Calcite and Dolomite - Benjamin R. Fosu; Josué J. Jautzy; Wenjun Yong; Richard A. Secco (Geochemistry, Geophysics, Geosystems, 2023)
Abstract Recent interlaboratory efforts have enabled methodological refinements in carbonate clumped isotope geochemistry, including the adoption of a carbonate‐based reference frame, the InterCarb Carbon Dioxide Equilibration Scale (I‐CDES). This calcite‐based standardization scheme aims at simplifying sample preparatory routines and ensuring identical treatment for all standards and unknowns. While the I‐CDES is a major step forward for the production of coherent results by laboratories for calcite, two aspects of this reference frame may only approximate but not ensure the principle of identical treatment of standards and unknowns because (a) the 90°C‐acid digestion temperature favored by I‐CDES is not achievable by all analytical setups and (b) the clumped isotope systematics of other carbonate minerals, if reported within a calcite reference frame only, may introduce uncertainties. We present an upgraded Kiel IV carbonate device—the “Franken‐Kiel”—performing acid digestions up to a theoretical 135°C, an enhancement over the factory‐default temperature of 70°C. The optimized setup considerably reduces the reaction time needed for digesting samples and yields good precision on Δ47 (i.e., long‐term standard deviations of 0.027 and 0.005‰ for calcite and dolomite standards, respectively). We further re‐evaluated the Δ47‐T relationship for calcite and dolomite directly in the I‐CDES and showed consistency between the produced temperature calibration and previous calibrations for calcite. We propose a mineralogy correction for dolomite in the I‐CDES that allows to partially reconcile theory with experimentation. Overall, the Franken‐Kiel showed excellent performance and warrants further tests on more recalcitrant carbonates, such as siderite and magnesite at higher acidification temperatures.